An ICT-FRET-based fluorescent probe for the ratiometric sensing of hypochlorous acid based on a coumarin–naphthalimide derivative. (17th March 2022) - Li, Lin-Ke; Hou, Yi-Min; Liu, Xiao-Chen; Tian, Mei-Ju; Ma, Qiu-Juan; Zhu, Nan-Nan; Liu, Shu-Zhen
Abstract : The probe displays a fast response time (< 2 s), high sensitivity and high selectivity for HOCl. Abstract : Hypochlorous acid (HOCl) is one of the most important reactive oxygen species (ROS) and plays an important role in pathological processes and relevant diseases. However, the highly sensitive/selective detection of HOCl with fast response time is still in demand. In this study, a ratiometric fluorescent probe for the highly selective detection of hypochlorous acid was constructed based on combined intramolecular charge transfer (ICT) and fluorescence resonance energy transfer (FRET) mechanisms. In the designed probe, a coumarin derivative was used as the energy donor and a naphthalimide fluorophore was chosen as the energy receptor, which was modified with a dimethylthiocarbamate group as a HOCl recognition unit. When HOCl was absent, the naphthalimide receptor underwent ICT off and the FRET process from the coumarin donor to the naphthalimide receptor was prevented. Upon adding HOCl, the naphthalimide receptor underwent ICT on and the FRET process took place. The ICT-FRET-based fluorescent probe for hypochlorous acid displayed high selectivity and very short response time (<2 s) and good biocompatibility. Furthermore, I 550nm / I 480nm of the probe for HOCl exhibited a good linear relationship in the range of 4.0 × 10 −7 –5.0 × 10 −5 mol L −1, and the detection limit of 2.5 × 10 −7 mol L −1 was achieved. Moreover, the probe demonstrated almost no cell toxicity and had been effectively applied to the ratiometric fluorescence imaging of HOCl in HeLa cells.